Fraus legis in land ownership conducted by foreign citizen in perspective of Indonesian land law - Rima Komariah; Djuhaendah Hasan; Siti Rodiah (Magister Kenotariatan Universitas Pasundan, 2022)
Indonesia has a close relationship with the earth, water, space, and the natural wealth contained therein, so the land tenure hierarchy in Indonesia places the nation's rights in the highest order. Based on the concept of the nation's rights, only Indonesian citizens are allowed to have full relations with the territory of Indonesia, while foreigners are not allowed. In practice, foreign nationals have abused their rights so that they can have land rights in the form of property rights in which there is a law smuggling action. One of the problems that arise is the recognition of ownership of land rights in the form of islands by foreign citizens. The purpose of this research is to analyze the ownership of land rights by foreign nationals associated with the abuse of rights by foreign nationals, the ownership of land rights in the form of islands by foreign nationals in the Indonesian land law system is associated with the right to control by the state and the concept of land rights. land in the form of islands in the Indonesian land law system. This research uses secondary data which is arranged in a systematic, comprehensive, and integrated manner to achieve clarity of the problem to be discussed. The results of the study show that foreign nationals can have land rights in the form of usage rights and rental rights. This policy is given the embodiment of the principle of justice. but is not allowed to have land rights in the form of property rights. In practice, there are many cases of abuse of rights by foreign nationals which are legal smuggling carried out through marriage, rental agreements with irrelevant terms, and control of usufructuary rights over a land area that violates the rules. The state's right to control land originates from the Indonesian nation's right to land. The state can grant land rights to foreign nationals as long as the land has not been granted other land rights.